The Effect of Systematic Corrective Exercises on the Ankle Proprioception in People with Functional Pronation Distortion Syndrome: A Randomized Controlled Clinical Trial Study - Ali Golchini; Nader Rahnama (Vesnu Publications, 2020)
Introduction: Pronation distortion syndrome is one of the most common abnormalities in the lower extremity that causes distortions in the structures of the skeletal parts of the foot. The purpose of this study was to determine the effect of systematic corrective exercises on the ankle proprioception in people with functional pronation distortion syndrome. Materials and Methods: In this randomized controlled clinical trial study, 30 volunteers who had pronation distortion syndrome were selected and randomly divided in to control and experimental groups. The experimental group performed corrective exercises for 12 weeks (3 sessions per week for one hour), while control group performed the routine exercises. Ankle proprioception (using electrogoniometer) was evaluated before and after the interventions. Data were analysed using independent and paired t tests. Results: Following 12 weeks of corrective exercises, the experimental group showed significant improvement in ankle proprioception (P = 0.001); however, there was no significant change in control group (P > 0.050). In addition, there was a significant improvement in ankle proprioception in the experimental group compared to control group (P < 0.001). Conclusion: It can be concluded that systematic corrective exercises improve ankle proprioception in patients with pronation distortion syndrome, and it may be recommended for these people.